A comprehensive description of the TolC effect on the antimicrobial susceptibility profile in Enterobacter bugandensis - Li, Bingyu; Zhang, Ji; Li, Xiaodong (Frontiers in Cellular and Infection Microbiology, 2022)
Background Enterobacter bugandensis is an emerging human pathogen in which multidrug resistant strains have been continuously isolated from various environments. Thus, this organism possesses the potential to pose challenges in human healthcare. However, the mechanisms, especially the efflux pumps, responsible for the multidrug resistance in E. bugandensis remain to be well elucidated. Methods The Enterobacter strain CMCC(B) 45301 was specifically identified using whole genome sequencing. The specific CMCC(B) 45301 homologues of the TolC dependent efflux-pump genes characterized in Escherichia coli were identified. The tolC deletion mutant in CMCC(B) 45301 was constructed and subjected to susceptibility tests using 26 different antimicrobial agents, along with the wild type strain. The synergistic effects combining the Bacillus crude extract (BCE) and several other TolC-affected compounds against CMCC(B) 45301 were assayed. Results We reclassified the Enterobacter CMCC(B) 45301 strain from species cloacae to bugandensis, on the basis of its whole genome sequence. We found that the CMCC(B) 45301 TolC, AcrAB, AcrD, AcrEF, MdtABC, EmrAB, and MacAB exhibit high similarity with their respective homologues in E. coli and Enterobacter cloacae. Our results for the susceptibility tests revealed that lacking tolC causes 4- to 256-fold decrease in the minimal inhibitory concentrations of piperacillin, gentamicin, kanamycin, tetracycline, norfloxacin, ciprofloxacin, chloramphenicol, and erythromycin against CMCC(B) 45301. In addition, the inhibition zones formed by cefuroxime, cefoperazone, amikacin, streptomycin, minocycline, doxycycline, levofloxacin, florfenicol, trimethoprim-sulfamethoxazole, azithromycin, lincomycin, and clindamycin for the tolC mutant were larger or more obvious than that for the parent. Our data suggested the important role played by TolC in CMCC(B) 45301 susceptibility to common antibiotic families covering ß-lactam, aminoglycoside, tetracycline, fluoroquinolone, phenicol, folate pathway antagonist, macrolide, and lincosamide. Deletion for tolC also increased the susceptibility of CMCC(B) 45301 to berberine hydrochloride and BCE, two natural product-based agents. Finally, we found that erythromycin, norfloxacin, and ciprofloxacin can potentiate the antibacterial activity of BCE against CMCC(B) 45301. Discussion The present study elaborated the comprehensive TolC effect on the antimicrobial susceptibility profile in E. bugandensis, which might contribute to the development of more therapeutic options against this nosocomial pathogen.